Global and local governance of shrimp farming in the Mekong Delta, Vietnam : - Tran, Thi Thu Ha (Wageningen University, 2012)
Contents: Genaral introduction; transformations of Vietnamese shrimp aquaculture policy; regulatory challenges certifying organic shrimp production; question the role cooperative shrimp aquaculture; general discussions and conclusions